The Detection and Primed Production of Novel Constructions. Issue 2 (June 2015) - McDonough, Kim; Fulga, Angelica
<x xml:space="preserve">Abstract</x> Situated within second language (L2) research about the acquisition of morphosyntax, this study investigated English L2 speakers' detection and primed production of a novel construction with morphological and structural features. We report on two experiments with Thai (n = 69) and Farsi (n = 70) English L2 speakers, respectively, carried out an aural construction learning task that provided low type‐frequency input with the transitive construction in Esperanto—which is marked by accusative case marking (–n) and flexible word order (subject‐verb‐object and object‐verb‐subject)—followed by aural comprehension tests and a priming activity (20 primes and 20 prompts). Results of the aural comprehension tests showed that 23% of the Thai participants (16/69) and 50% of the Farsi participants (35/70) detected the target construction in the input. Results of the primed production task revealed that only those participants who detected the target construction were able to be primed. The findings are discussed in relation to the role of speakers' previously learned languages in the detection and primed production of novel constructions.